2014
DOI: 10.3390/vaccines2020354
|View full text |Cite
|
Sign up to set email alerts
|

HIV DNA Vaccine: Stepwise Improvements Make a Difference

Abstract: Inefficient DNA delivery methods and low expression of plasmid DNA have been major obstacles for the use of plasmid DNA as vaccine for HIV/AIDS. This review describes successful efforts to improve DNA vaccine methodology over the past ~30 years. DNA vaccination, either alone or in combination with other methods, has the potential to be a rapid, safe, and effective vaccine platform against AIDS. Recent clinical trials suggest the feasibility of its translation to the clinic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 208 publications
1
36
0
1
Order By: Relevance
“…It can be used as a stand-alone platform or it can be combined with other vaccine modalities (viral vectors, protein), transfer of bNab, and molecular adjuvants (for reviews see [49][50][51][52][53]. We have demonstrated that HIV/SIV pDNA vaccines induce responses, including CE-induced (X. Hu, A. Valentin, and B.K.…”
Section: Discussionmentioning
confidence: 99%
“…It can be used as a stand-alone platform or it can be combined with other vaccine modalities (viral vectors, protein), transfer of bNab, and molecular adjuvants (for reviews see [49][50][51][52][53]. We have demonstrated that HIV/SIV pDNA vaccines induce responses, including CE-induced (X. Hu, A. Valentin, and B.K.…”
Section: Discussionmentioning
confidence: 99%
“…Live-attenuated vaccines showed promising levels of protection in NHP models [13,15]; however, they were associated with irreversible integration in the host genome, persistence and reversion to pathogenic state in some vaccinated animals [16,17] impelling safer strategies for clinical use. Alternatively, DNA vaccines became more attractive tools for vaccination against HIV and other pathogens, particularly with effort being made to increase their immunogenicity via optimizing vaccine design, use of adjuvants, and delivery methods [43][44][45][46][47].…”
Section: Discusionmentioning
confidence: 99%
“…The versatility of DNA-based vaccines is particularly attractive for countering HIV-1 infection [15]. As with all such antiviral approaches, induction of a high level of transgene expression is vital to inducing an effective immune response.…”
Section: Transfer Of Genes Encoding Immunogenic Hiv-1 Proteinsmentioning
confidence: 99%
“…viral sequences on protein translation [15]. After intramuscular injection, the antibody or antibody-like protein is expressed, secreted, and is then available to neutralize exposure to the virus.…”
Section: Transfer Of Genes Encoding Immunogenic Hiv-1 Proteinsmentioning
confidence: 99%